Upaya Peningkatan Pengetahuan Terhadap Manajemen Luka Bakar Derajat 1 di SMP Muhammadiyah 1 Gading Rejo - Afikirtiani, Winda; Meidas Setia, Vovi; Nurrohmah, Nisa; HS, Asril (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Burns are one of the most common injuries in school-aged children and are often treated inappropriately. Education on the management of minor burns is essential so that students have the knowledge and skills to perform proper first aid. Objective: To assess the effectiveness of a 1st degree burn management education program on improving the knowledge and preparedness of junior high school students in dealing with burn incidents. Method: This activity was carried out in the form of community service at SMP Muhammadiyah 1 Gading Rejo, Lampung, with a participatory educational approach through counseling, leaflets, interactive discussions, and pre-test and post-test evaluations. The targets of the program were 50 seventh grade students. Result: This activity can improve participants' understanding of the causes, types, severity of burns, and correct initial handling procedures with an average frequency of pre-test knowledge level of 54% and an average frequency of post-test knowledge level of 78%. There was a significant increase in participants' knowledge of burns, including burn treatment, burn characteristics, and how to prevent burns with good and correct procedures. Conclusion: This educational program was effective in increasing students' awareness and skills in managing minor burns. It is recommended that similar programs be implemented regularly and expanded to other schools.